que espressao algébrica deve ser adicionado a a2+6a2b2-12a2b para obter o quadrado de (2a-3ab)
Anexos:
![](https://pt-static.z-dn.net/files/dc8/43dc04dd50b0482cf7a8e536071693bd.jpg)
Soluções para a tarefa
Respondido por
5
(2a - 3ab)²= 4a² -12a²b + 9a²b²
4a² - 12a²b + 9a²b² + Expressão=a²+6a²b²- 12a²b
Expressão=a²+6a²b²-12a²b -(4a²-12a²b+9a²b²)
Expressão=a²+6a²b²-12a²b-4a²+12a²b-9a²b²
Expressão=-3a²-3a²b²
stefanny964:
vc me salvou
Perguntas interessantes
Filosofia,
10 meses atrás
Sociologia,
10 meses atrás
Química,
10 meses atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Saúde,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás